An Interactive Multimedia Tutorial to Teach Examination of the Thorax, Lungs and Abdomen : Final Report for Project no. 3007/2'. - Huynh, Mary; Bauer, Michael; Brown, Vera (Committee for University Teaching and Staff Development (CUTSD), 2000)
This is a final report for a 1998 National Teaching Development Grant funded by the Committee for University Teaching and Staff Development. The project was concerned with the production of an interactive multimedia tutorial to teach examination of the thorax, lungs and abdomen to nursing students. The report describes the project, outlining the aims, background and implementation of the CD-ROM and provides a project evaluation and discussion of results.